Projekty i ich realizacja w szkołach muzycznych = The implementation of educational projects at music schools - Gubała, Monika (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Educational projects are an interesting form of school activities. They develop the students not only musically, but also - through integration of all groups within a school - socially. The paper presents an educational project as a pro-social activity in the sphere of culture and an example of social participation, based on case study of the "Musical postcards" musical-children`s opera carried out by the Primary Music School in Dobczyce.
Keywords: kultura; projekt edukacyjny; szkoła muzyczna; culture; educational project; music school